Baanyan Pottery Crafts as Wetland-Based Creative Economy Industry - Riski Ramadani; Melly Agustina Permatasari; Syaharuddin Syaharuddin; Muhammad Fajar Maulan; Muhammad Fazrur Rahman Fadhil (Universitas Lambung Mangkurat, 2026)
Pottery craft in Baanyan Village, South Daha District, Hulu Sungai Selatan Regency, represents a form of creative economy deeply rooted in the local wisdom of wetland communities, preserved and practiced across generations. This study aims to describe the production process, product types, sustainability challenges, and development opportunities of pottery craft as a wetland-based creative industry. A descriptive qualitative approach was employed through in-depth interviews, participatory observation, and document analysis conducted directly with artisans at the production site. The findings reveal that the swamp ecosystem provides high-quality clay as the primary raw material through natural river sedimentation processes. Products include ritual burial jars (guci) used for placenta burial ceremonies, traditional cooking stoves (atang), and decorative piggy banks (celengan), with an average production capacity of 100 units per day. The production process is highly dependent on the dry season for drying and firing stages, making indigenous knowledge of seasonal cycles a vital production calendar for local artisans. However, this craft faces serious challenges, including river environmental degradation that threatens raw material availability, a regeneration crisis driven by declining interest among younger generations, and an over-reliance on seasonal middlemen that limits broader market access. On the other hand, the rapid growth of digital platforms and e-commerce presents significant opportunities for expanding markets at both national and global levels. This study contributes to strengthening the discourse on wetland-based creative economy sustainability while offering institutional recommendations to preserve pottery craft as a cultural identity of swamp-dwelling communities